Perceived quality in assistance services in older adults - Ernesto López González; Yolanda Cabrera Macias; Ernesto López Cabrera; Anaily Puerto Becerra (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
The perceived quality applied to services has become a strategic priority; the evaluating process from the user and provider satisfaction dimensions is of great importance, which implies to contribute to it, applying the most advanced of the procedures used in the health sector. The objective of this work is to explain how the dimension user and provider satisfaction of assistance to older adults, is essential for quality evaluation if done from their voices on the bases of updated instruments and procedures. Determining the present situation of the perceived quality, emphasizing in the provider and user in the assistance of older adults, will allow specifying the main limitations and potentials of these services, taking as theoretical foundation those which internationally support their evaluation. Measuring it contributes to the efficiency, decision making and the intelligent use of the resources in the organizations.